Preparation and evaluation of reduced graphite oxide for oil spill removal - Hussain, Intesar Razaq (2016)
The production of reduced graphite oxide, graphite oxide and their associates has sparked the interests of the nanomaterials scientists and engineers for the past decade. With their superior properties, these materials can be functionalized or modified to fit specific applications from nanocomposites to smart and functionalized materials. The typical and most efficient reduction agent used is Hydrazine Hydrate (N2H4), a highly toxic chemical. The objectives of this work were to synthesize and characterize the hierarchical and porous structure of reduced graphite oxide using reduction integrated chemical treatment methods. In addition, this study aimed to evaluate the potential of reduced graphite oxide as an absorbent for oil spill removal. Graphite Oxide was synthesized using the modified Staudenmaier‘s method and chemically reduced using 30% heated Ammonia solution (NH3) at 90˚C. Different chemical treatments were done namely leavening method (10 hours) and spaced method (5, 10 and 17 hours using either soxhlet or rotary evaporator). A two-step reduction (calcination of reduced graphite oxide (4 hours) under a nitrogen atmosphere at 500oC) was also done. For the oil removal test, crude oil was recovered from a simulated sample and the absorbent was regenerated by washing it in hexane. The GO and rGO products were characterized using different characteristic tools. In general, it was found that different methods produced reduced graphite oxide with different properties even though the same reducing agent was used throughout the experiment. The results showed that rGO paper lost most of O-H functional groups, less defects and more thermally stable compared to GO. The percentage of impurities was significantly reduced from 15.37 for graphite oxide to 0.23 for calcined reduced graphite oxide. All the reduced graphite oxide papers produced in this study had a density that was lighter than water. They are also hydrophobic and super oleophilic with a contact angle 120o. The produced materials were able to absorb oil up to 41.3 g g-1, while completely repelling water. The reusability test for the reduced graphite oxide paper was conducted for five cycles. It was found that the reduction in the absorption efficiency was from 3.5% to 4% after each cycle. This indicates that the paper could be used more than five times in the oil removal process. In addition, the efficiency of the COD removal was 95%. This work had demonstrated effective methods to prepare the reduced graphite oxide paper. It offers a new alternative methods using either direct contact with ammonia vapor only or with both ammonia liquid and vapor, at a much lower temperature 90˚C and can be produced at ambient pressure. The material also showed a strong potential as an absorbent for oil spill removal